2016
DOI: 10.1155/2016/2068691
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Receptors in Focal Segmental Glomerulosclerosis: A Review on the Scientific Point of View

Abstract: Focal segmental glomerulosclerosis (FSGS) is one of the primary glomerular disorders in both children and adults which can progress to end-stage renal failure. Although there are genetic and secondary causes, circulating factors have also been regarded as an important factor in the pathogenesis of FSGS, because about 40% of the patients with FSGS have recurrence after renal transplantation. Soluble urokinase-type plasminogen activator receptor (suPAR) is a soluble form of uPAR, which is a membrane-bound protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 109 publications
1
37
0
Order By: Relevance
“…The majority of the patient samples examined here also caused a substantial loss of podocin in cultured podocytes, consistent with previous reports [44,46]. Similar effects on TRPC6 and podocin were evoked by suPAR, a circulating factor that has been suggested to drive primary and recurrent FSGS [5,57] and which markedly increases risk for future chronic kidney disease [1012]. However, not all of the recurrent FSGS plasma samples showed this pattern.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of the patient samples examined here also caused a substantial loss of podocin in cultured podocytes, consistent with previous reports [44,46]. Similar effects on TRPC6 and podocin were evoked by suPAR, a circulating factor that has been suggested to drive primary and recurrent FSGS [5,57] and which markedly increases risk for future chronic kidney disease [1012]. However, not all of the recurrent FSGS plasma samples showed this pattern.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, some patients with high total serum suPAR levels from other causes, such as in certain cancers, do not show signs of glomerular dysfunction [57]. It is possible that in a generally inflammatory milieu, for example in various forms of glomerulonephritis, suPAR signaling would be more deleterious as compared to children or young adults with primary nephrotic syndromes in which inflammation is generally not present.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis linking suPAR to podocyte injury and FSGS has great potential to advance our limited understanding of the mechanisms of primary FSGS. The role of suPAR in recurrent FSGS in particular and in podocyte injury in general has remained controversial, as summarized in two recent reviews (8,9) and a letter to the editor (10). Some researchers have not been able to replicate these findings with regard to the colleagues recently demonstrated that suPAR causes activation of podocyte TRPC6 channels, resulting in calcium ion influx.…”
Section: Supar Rna Isoform 2 Overexpression Induces Proteinuria and Fsgsmentioning
confidence: 99%
“…However, the study of Hahm and colleagues demonstrates the occurrence of proteinuria after bone marrow transplantation in Plaur −/− mice only 1,2 . Previous studies by ourselves and others suggest that soluble urokinase plasminogen activator receptor (suPAR) might induce proteinuria in Plaur −/− mice but not in wildtype animals [3][4][5] . The reason for this discrepancy is unclear, but the possibility exists that lack of uPAR might induce constitutive and secondary changes, such as overexpression of β3 integrins on podocyte membranes, that lead to an explosive response to exogenous suPAR.…”
mentioning
confidence: 99%